Fictions of affliction : physical disability in Victorian culture - Stoddard Holmes, Martha (Corporealities., 2004)
"We all know Tiny Tim, that familiar Victorian figure of infirmity, sentimentality, and charity: why do so many of the most memorable fiction characters in nineteenth-century British literature have disabilities? What did physical disability mean to people in Victorian Britain - and what can that meaning teach us about Victorian culture? In Fictions of Affliction, Martha Stoddard Holmes seeks to answer these questions by investigating works of drama and fiction and other writing of the period, including the personal testimony of Victorians with disabilities. Holmes finds that melodramatic representations of disability pervaded not only novels by Dickens, but also doctors' treatises on blindness, educators' arguments for "special" education, and even the writing of disabled people themselves."--Jacket